3-Hydroxyphthalic Anhydride-Modified Chicken Ovalbumin as a Potential Candidate Inhibits SARS-CoV-2 Infection by Disrupting the Interaction of Spike Protein With Host ACE2 Receptor - Liang, Taizhen; Qiu, Jiayin; Niu, Xiaoge; Ma, Qinhai; Zhou, Chenliang; Chen, Pei; Zhang, Qiao; Chen, Meiyun; Yang, Zifeng; Liu, Shuwen; Li, Lin (Frontiers in Pharmacology, 2021)
The global spread of the novel coronavirus SARS-CoV-2 urgently requires discovery of effective therapeutics for the treatment of COVID-19. The spike (S) protein of SARS-CoV-2 plays a key role in receptor recognition, virus-cell membrane fusion and virus entry. Our previous studies have reported that 3-hydroxyphthalic anhydride-modified chicken ovalbumin (HP-OVA) serves as a viral entry inhibitor to prevent several kinds of virus infection. Here, our results reveal that HP-OVA can effectively inhibit SARS-CoV-2 replication and S protein-mediated cell-cell fusion in a dose-dependent manner without obvious cytopathic effects. Further analysis suggests that HP-OVA can bind to both the S protein of SARS-CoV-2 and host angiotensin-converting enzyme 2 (ACE2), the functional receptor of SARS-CoV-2, and disrupt the S protein-ACE2 interaction, thereby exhibiting inhibitory activity against SARS-CoV-2 infection. In summary, our findings suggest that HP-OVA can serve as a potential therapeutic agent for the treatment of deadly COVID-19.